The interplay between methodologies, tasks and visualisation formats in the study of visual expertise - Boucheix, Jean-Michel (Frontline Learning Research, 2017)
The author examines the methodological contributions of the ten unique reviews developed in this special issue on the methodologies for studying visual expertise. Opportunities, research results and lessons, offered by each methodology are analyzed according to four dimensions criteria: (i) The different levels of visual and cognitive processes targeted in the different methods; (ii) The effect of the task gaols and task design on the outcomes; (iii) The potential effect of the format (dynamic versus static) of the visual material and the interactive features provided in previous studies (iv) The potential modulating effect of learners individual differences. Concluding comments are developed about the limitations of each method but also about the challenge and promises of designing and using combined and synchronized methods.